Dinamiche migratorie e capitale sociale territoriale: aspetti teorici e metodologici - Michela Lazzeroni; Monica Meini (Bollettino della Società Geografica Italiana)
This article focuses on the relationship between migratory phenomena and geographical contexts, trying to draw an interpretative framework for the analysis of the social capital in the embedding processes of the immigrant foreign population at local level. To this purpose, the notion of social capital is firstly reinterpreted by emphasizing the territorial dimension and the link with the geographic, political-economic and cultural components that influence migration choices and integration processes. Secondly, the methodological tools used to analyze the relationship between migration dynamics and the existing social capital in a specific territory are identified, paying attention to the territorialization processes and the contribution of immigrants to the construction and transformation of places and communities of destination. In particular, the role of second generations is detected, both in building territorial networks and social and cultural interaction and in the dynamics of interconnection between local and translocal relations. Finally, some results of an extensive survey are illustrated in which the proposed comparative methodology has been applied to different territorial contexts of nine Italian regions.